Impact of pancreatic cell-engineered constructs on the islet apparatus in recipient rats with type I diabetes mellitus - N. V. Baranova; L. A. Kirsanova; G. N. Bubentsova; A. S. Ponomareva; A. O. Nikolskaya; Yu. B. Basok; V. I. Sevastianov (Вестник трансплантологии и искусственных органов, 2025)
Current research focuses on exploring strategies to stimulate the regenerative capacity of pancreatic beta cells as a potential therapeutic approach for diabetes mellitus (DM).Objective: this study aims to perform a comparative histological analysis of the islet apparatus in rats with streptozotocin (STZ)-induced DM following the implantation  of a pancreatic cell-engineered construct (PCEC). The PCEC consists of isolated allogeneic islets of Langerhans embedded within a scaffold derived from decellularized human pancreatic fragments.Materials and methods. The pancreases of rats from the control group (n = 4; untreated type 1 DM – T1DM), experimental group 1 (n = 4; intraperitoneal injection of pancreatic islets), and experimental group 2 (n = 4; intraperitoneal injection of PCEC) underwent histological analysis. Immunohistochemical staining for insulin and glucagon was performed using specific antibodies and an imaging system.Results. In the pancreatic islets of the control group, insulin- immunopositive beta cells were either absent or detected as isolated cells, with alpha cells predominating. In the pancreases of experimental group 1 rats, beta cells were observed in most islets and within the surrounding exocrine parenchyma, albeit in low numbers (1–2 per field of view), while alpha cells remained the dominant population. A significant increase in insulin-positive cells was observed in the pancreas of rats in experimental group 2, along with a reduction in glucagon-positive cell numbers.Conclusion. Morphological examination of the pancreatic islet apparatus in the experimental animals revealed that implantation of the PCEC had a be- neficial effect on restoration of the recipient’s pool of functionally active beta cells, serving as a trigger for the regenerative process.